The Investigation of How Anxiety Never Stops Me from Learning English: An Autoethnography Research - Marshalina, Afifah (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
As one of the most crucial affective variables, anxiety is a highly significant predictor of EFL, which may hinder the learning process. This paper presents an autoethnography qualitative investigation of the journey of learning English, which has been dominated by anxiety. The researcher’s learning experiences since secondary school were discovered. This paper aimed to explore central research questions of the cause of anxiety and the strategy to cope with anxiety in learning English. In this autoethnography, personal memories served as the primary instrument for data collection, supplemented by visual data such as pictures, a drawing, diary snippet, and screenshots. Finding crucial moments and doing in-depth analysis become considerably important in using autoethnography. Furthermore, this paper employed a narrative approach to describe personal experiences and used thematic analysis to categorize data based on key themes in findings. The study findings indicated that lack of teacher encouragement, unpleasant classroom atmosphere, lack of vocabulary mastery, and fear of negative evaluation became the causes of anxiety. In addition, several ways to cope with anxiety done through keeping a positive mindset, improving self-motivation to learn more, and involving in the English community. Implications and suggestions for potential further study are also addressed.